2016
DOI: 10.1590/0001-3765201620140574
|View full text |Cite
|
Sign up to set email alerts
|

The anti-inflammatory activity of standard aqueous stem bark extract of Mangifera indica L. as evident in inhibition of Group IA sPLA2

Abstract: The standard aqueous stem bark extract is consumed as herbal drink and used in the pharmaceutical formulations to treat patients suffering from various disease conditions in Cuba. This study was carried out to evaluate the modulatory effect of standard aqueous bark extract of M. indica on Group IA sPLA 2 . M. indica extract, dose dependently inhibited the GIA sPLA 2 (NN-XIa-PLA 2 ) activity with an IC 50 value 8.1 μg/ml. M. indica extract effectively inhibited the indirect hemolytic activity up to 98% at ~40 μ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 51 publications
0
11
0
3
Order By: Relevance
“…Several studies showed that phytochemicals contained in mango play an anti-inflammatory role in several chronic pathological disorders associated with inflammatory responses [38,39]. Inflammatory bowel diseases, primarily including ulcerative colitis, are disorders that are characterised by chronic inflammation and mucosal damage in the large intestine.…”
Section: Anti-inflammatory Effects Of Mangomentioning
confidence: 99%
“…Several studies showed that phytochemicals contained in mango play an anti-inflammatory role in several chronic pathological disorders associated with inflammatory responses [38,39]. Inflammatory bowel diseases, primarily including ulcerative colitis, are disorders that are characterised by chronic inflammation and mucosal damage in the large intestine.…”
Section: Anti-inflammatory Effects Of Mangomentioning
confidence: 99%
“…Mangifera species is a tropical plant that is proven to have pharmacological properties such as anti-diabetic [13], anti-cancer [14], anti-inflammatory [15], and the ability to attenuate kidney damage [16]. The mango fruit ( Mangifera indica L.) and its wastes, is one of the extensively studied Mangifera species, owing to abundant nutrients and phytochemicals that benefits human health [17].…”
Section: Introductionmentioning
confidence: 99%
“…Calpactins usually bind calcium ion and also phospholipid ion. it has been suggested that this property of Calpacitns direct inhibition of phospholipase A2, and also responsible for the reduction in eicosanoid formation [55][56][57].…”
Section: The Mechanism Of Action Of Steroids In Inflammationmentioning
confidence: 99%